2013
DOI: 10.5005/jp-journals-10005-1211
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coconut Water and Jordanian Propolis on Survival of Bench-dried Periodontal Ligament Cells: Anin vitro Cell Culture Study

Abstract: Aim: The aim of this study is to assess and compare the efficacy of Jordanian propolis and full concentration mature coconut water in their ability to preserve periodontal ligament (PDL) cell viability after exposure of PDL cells to up to 120 minutes dry storage.Materials and methods: PDL cells were obtained from sound permanent first molars which were cultured in Dulbecco's Modified Eagles Medium (DMEM). Cultures were subjected to 0, 30, 45, 60, 90 and 120 minutes dry storage times then incubated with 100% ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Avulsion of permanent tooth is considered the most serious traumatic injury resulting in aesthetic, functional and psychological problems to injured patient (37,38) . The recommended treatment in such case is instant replantation of the dislodged tooth; however, it is not always possible to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Avulsion of permanent tooth is considered the most serious traumatic injury resulting in aesthetic, functional and psychological problems to injured patient (37,38) . The recommended treatment in such case is instant replantation of the dislodged tooth; however, it is not always possible to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Contiene aminoácidos, oligoelementos, vitaminas, minerales y aceites esenciales Gracias a la acción antibiótica del propóleo, que protege de la actividad de virus y bacterias, la colmena es uno de los lugares más estériles conocidos en la naturaleza. No obstante, estudios científicos han demostrado que el efecto del propóleo se consigue gracias a la acción sinérgica de todos sus componentes y concluyen que es tan efectivo como la leche y el HBSS (18,27,30,31,34). Leche: En 1981 Andreasen (Dinamarca) y Blomlof, Lindskog y Hammarstrom (Suecia) fueron los primeros en reportar sobre la viabilidad de la leche fresca descremada pasteurizada como medio para conservar un diente avulsionado.…”
Section: Medios De Almacenamientounclassified
“…Ahangari Z en su artículo del 2013 concluye que hay una alta tasa de éxito que se puede conseguir cuando los dientes avulsionados se mantienen en condiciones húmedas y llevados a una clínica dental tan pronto como sea posible (31). EN 2013 Al-Haj Ali SN en un artículo y de Paula Reis MV en otro publican que el Aloe Vera al 10, 30 y 50% puede ser recomendado como medio de almacenamiento celular (27,28). En el mismo artículo del 2013 de Paula Reis MV propone el agua de coco y la leche de soja como medios de almacenamiento debido a sus nutrientes las cuales conservan la viabilidad celular El agua de coco resultaría ser un medio de almacenamiento prometedor para los dientes avulsionados Los estudios indicaron que el grupo de agua de coco demostró un número significativamente mayor de células PDL viable que el propoleo (28,30).…”
Section: Revista Evidencias En Odontología Clínicaunclassified
“…The results showed that avulsed teeth, which have been left dry for more than 45 minutes, soaked in mature coconut water for 45 minutes in mature coconut water could be beneficial. 31 Prueksakorn et al 32 examined the preservative and proliferative effects of Thai propolis extract. Their results exhibited that 2.5 mg ml-1 of Thai propolis was the appropriate dose for preserving the viability of PDL cells, and it was comparable to Hanks Balanced Salt Solution (HBSS).…”
Section: Storage Mediummentioning
confidence: 99%